Synthesis, characterization, and hyperpolarizability measurements of main-chain azobenzene molecules - Smitha, P.; Asha, S. K.; Pillai, C. K. S. (Journal of Polymer Science Part A: Polymer Chemistry, 2005)
A series of new AB type azobenzene monomers based on various substituted phenols and higher order fused/extended aromatic rings were synthesized and their hyperpolarizability tensor β determined by hyper-Rayleigh scattering (HRS) measurement in methanol. The electron donor ([BOND]OH) and acceptor units ([BOND]COOH) were kept constant in the series, but the effective conjugation length was varied by varying the number and position of substituents as well as the number of aromatic rings. The effect of substitution of the phenolic ring on the β value was investigated and it was found to range from 15 × 10−30 to 42 × 10−30 esu. The effect of intramolecular hydrogen bonding on the nonlinear optical (NLO) property was also examined. The nonlinearity was in the following order of phenol derivative: α-naphthol > phenyl phenol > 2,6-dimethyl phenol > o-cresol > cardanol > phenol > β-naphthol. The unusually low values for the β-naphthol-based chromophore compared with its isomer (α-naphthol) could be rationalized based on hydrogen bonding of the o-hydroxyl group with the β nitrogen of the azo bridge. These azobenzene NLO chromophoric monomers were polymerized to form main-chain polymers with a head to tail structure. The polymers had high thermal stability and rather low solubility in common organic solvents. © 2005 Wiley Periodicals, Inc. J Polym Sci Part A: Polym Chem 43: 4455–4468, 2005